The Effectiveness of PET-Scan in Diagnosis and Treatment of Non-Small Cell Lung Carcinoma (NSCLC) and Lymphoma: A Comprehensive Review of Literature - Hamid Ravaghi; Ali Akbari Sari; Sima Sarvari; Mohammad Reza Mobinizadeh (مجله دانشکده پزشکی اصفهان, 2012)
Background: Positron emission tomography (PET) scan is a non-invasive, complicated and expensive medical imaging technology used for diagnosis and treatment of various diseases including cancers. This study aimed to evaluate the safety and effectiveness of this technology. Methods: The major medical electronic databases including Cochrane Library, Google Scholar, MEDLINE and IranMedex were searched. The studies that compared PET-scan with other diagnostic methods in terms of sensitivity, specificity and safety were considered in this review. Findings: PET-scan has been found to be a non-invasive and safe procedure for diagnosing metastatic NSCLC with a sensitivity and specificity of 74-95% and 81-97%, respectively. On the other hand, the sensitivity and specificity of computed tomography (CT) scan have been reported as 60-67% and 73-77%, respectively. The corresponding values for mediastinoscopy have been 78% and 100%. In lymphoma, the specificity and sensitivity of PET-scan (90% and 79-100%, respectively) have been higher than those of gamma scan. Although PET-scan is not an appropriate method for screening and diagnosis of cancer, it can contribute to staging and follow-up processes in cases of NSCLC and lymphoma. This technology adds 0.046 years (about 17 days) to the patient's life. Conclusion: PET-scan is a safe technology that has better diagnostic performance in comparison with similar technologies. The application of this method in staging and follow-up of NSCLC and lymphoma can prevent unnecessary surgeries and add a few years to the lives of patients.